음악 작품으로 본 셰익스피어(William Shakespeare)의 영향력과 영감 - 길한나(Hanna Kiel) (한국콘텐츠학회 논문지, 18(4), 2018)
This paper reevaluates the influence and value of Shakespeare inherent in the history of music, focusing on the works of playwright William Shakespeare who have had an absolute influence on the history of music and various musical works derived from his work. To consider ways referred to the original work of Shakespeare, and at the same time to analyze the different musical pieces with his same material, and also about the musical implementation according to theatrical devices provided by Shakespeare through the four aspects of 'Shakespeare's musical descriptions and texts', 'Configuration model and its variants', 'Portrayal of person and human character' and 'Genre diversity and Creative possibility'. 이 논문은 음악사에 절대적 영향을 끼친 극작가 윌리엄 셰익스피어(William Shakespeare)의 작품들을 토대로 탄생한 다양한 음악작품을 중심으로 음악사 안에 내재된 셰익스피어의 영향력과 가치를 재조명한다. 그 방법으로 셰익스피어의 원작을 언급함과 동시에 동일 소재를 사용한 서로 다른 음악 작품들을 분석하며, 또한 셰익스피어가 제공한 극적 장치에 따른 음악적 구현에 관하여 '셰익스피어의 음악적 언급과 텍스트', '구성적 본보기와 그 변형', '인물묘사와 인간상의 구현', '장르적 다양성과 창조적 가능성' 등 네 가지 측면을 통하여 고찰한다.